Sex hormones shape EEG-based functional connectivity in early-stage Parkinson’s disease patients - Matteo Conti; Roberta Bovenzi; Mariangela Pierantozzi; Clara Simonetta; Valerio Ferrari; Jacopo Bissacco; Rocco Cerroni; Claudio Liguori; Francesca Di Giuliano; Nicola Biagio Mercuri; Tommaso Schirinzi; Alessandro Stefani (NeuroImage: Clinical)
Parkinson’s disease (PD) epidemiology and clinical features are sexually dimorphic. However, there are no data based on EEG functional connectivity (FC). Likewise, the contribution of sex hormones on brain FC has never been evaluated. Here, we aimed to investigate the association between biological sex and sex hormones on cortical FC changes in PD using high-density EEG. This study involved 69 early-stage PD patients (F/M 27/42) and 69 age-matched healthy controls (HC) (F/M 30/39). Sex hormone levels (total-testosterone (TT), estradiol (E2), follicle-stimulating hormone (FSH), and luteinizing hormone (LH)) were assessed in PD patients. Data were recorded with a 64-channel EEG system. Source reconstruction method was used to identify brain activity. Cortico-cortical FC was analysed based on the weighted phase-lag index (wPLI) in θ-α-β-low γ bands. Network-based statistic (NBS) was used to compare FC between genders in HC and PD and to study the relationship between FC and sex hormones in PD. PD exhibited a hypoconnected network at θ and α bands and a hyperconnected network at β band compared to HC. Male HC showed a hyperconnected network at α-band compared to female HC. Conversely, males with PD showed a hypoconnected network at α-band compared to females with PD. In females and males with PD, E2 positively correlated with α-FC, while gonadotropins positively correlated with β-FC. TT positively correlated with the θ-FC only in males. Sex hormones shape EEG-FC in both males and females with PD, supporting their major influence on PD pathophysiology.